Correction: Jiang et al. A Cloud Classification Method Based on a Convolutional Neural Network for FY-4A Satellites. Remote Sens. 2022, 14, 2314 - Yuhang Jiang; Wei Cheng; Feng Gao; Shaoqing Zhang; Shudong Wang; Chang Liu; Juanjuan Liu (Remote Sensing, 2023)
In the original publication [...]